STYLE AND TIMING OF SALT TECTONICS IN THE DNIEPR-DONETS BASIN (UKRAINE): IMPLICATIONS FOR TRIGGERING AND DRIVING MECHANISMS OF SALT MOVEMENT IN SEDIMENTARY BASINS - Stovba S.M.; Stephenson R.A. (My University, 2002)
The Ukrainian Dniepr-Donets Basin (DDB) is a Late Palaeozoic intracratonic rift basin, with sedimentary thicknesses up to 19 km, displaying the effects of salt tectonics during its entire history of formation, from Late Devonian rifting to the Tertiary. Hundreds of concordant and discordant salt structures formed during this time. It is demonstrated in this paper that the variety of styles of salt structure formation in the DDB provide important constraints on understanding the triggering and driving mechanisms of salt kinematics in sedimentary basins in general. Salt movement in the DDB began during the Devonian syn-rift phase of basin development and exerted controls on the later distribution of salt structures though the geometry of basement faults is not directly responsible for the regular spacing of salt structures. Post-rift salt movements in the DDB occurred episodically. Episodes of salt movement were triggered by tectonic events, specifically two extensional events during the Carboniferous, an extensional reactivation at the end of Carboniferous–earliest Permian, and a compressional event at the end of the Cretaceous. Extensional events that induced salt movement were ‘thick-skinned’ (i.e. basement involved in deformation) rather than ‘thin-skinned’. Most overburden deformation related to salt movements is ductile regardless of sedimentary bulk lithology and degree of diagenesis, while the deformation of sedimentary cover in areas where salt is absent is mainly brittle. This implies that the presence of salt changes the predominant mode of deformation of overlying sedimentary rocks. Episodes of salt movement lasted longer than the periods of active tectonics that initiated them. Buoyancy, erosion, and differential loading all played a role in driving halokinesis once tectonic forces had pushed the salt-overburden system into disequilibrium; among these factors, erosion of overburden above growing salt structures acted as a key self-renewing force for development of salt diapirs. Very high sedimentation rates (related to high post-rift tectonic subsidence rates), particularly during the Carboniferous, were able to bury diapirs and to load salt bodies such that buoyancy, erosion, and differential loading forces eventually became insufficient to continue driving diapirism—until the system was perturbed by an ensuing tectonic event. In contrast, some salt anticlines and diapirs developed continuously during the entire Mesozoic because of much-reduced tectonic subsidence rates (and sedimentation supply) during this time. However, a Lower Permian salt series and overhangs of buried diapirs played an important role in preventing overburden piercing (and fracturing) during the Mesozoic and, specifically, during the Late Cretaceous salt diapirism phase.